Proceedings of the Canadian Society of Civil Engineering Annual Conference 2021 CSCE21 Hydrotechnical and Transportation Track - Walbridge, Scott; Nik-Bakht, Mazdak; Ng, Kelvin Tsun Wai.; Shome, Manas; Alam, M. Shahria; El Damatty, Ashraf; Lovegrove, Gordon; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book comprises the proceedings of the Annual Conference of the Canadian Society of Civil Engineering 2021. The contents of this volume focus on specialty conferences in construction, environmental, hydrotechnical, materials, structures, transportation engineering, etc. This volume will prove a valuable resource for those in academia and industry.
Chapter 1: Design Of Roundabout To Replace All-Way Stop Controlled Intersection: Case Study In Niagara-On-The-Lake -- Chapter 2: Valuing Demand Response On Electric Vehicles Charging -- Chapter 3: The Role Of Microplastics$1 (BSize And Density On Their Vertical Turbulent Mixing And Transport -- Chapter 4: Surrogate Model Development For Bioretention Cell Simulation-Optimisation Applications.s
Keywords: Building materials; Engineering geology; Transportation engineering; Traffic engineering; Environmental engineering; Civil engineering; Building Materials; Geoengineering; Transportation Technology and Traffic Engineering; Environmental Civil Engineering; Transportation engineering -- Congresses; Hydraulic engineering -- Congresses